Pengaruh Keyakinan Pancasila Sebagai Ideologi Negara Terhadap Penolakan Paham Radikalisme Program Studi Pendidikan Administrasi Perkantoran Stambuk 2024 : Penelitian - Guruh Real Agave Nababan; Addina Olivia Saragih; Fitri Yani Nur Fatimah Ritonga; Michaelin Esteria Br Simanjuntak; Nurlita Safrani; Nazla Aprilia; Mutia Zahra; Ibnu Sina; Julia Ivanna (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to determine the extent to which students' belief in Pancasila as the state ideology influences their attitudes in rejecting radicalism. The study was conducted with a quantitative approach using a survey method through a Likert scale questionnaire given to 35 students of the Office Administration Education Study Program, Stambuk 2024, selected by simple random sampling. Data were analyzed using simple linear regression to see the relationship between the two variables. The results showed that students have a high level of belief in Pancasila and a strong attitude of rejection of radicalism. The R² value of 0.64 indicates that 64% of the variation in rejection of radicalism is influenced by the level of belief in Pancasila, with a positive and significant regression coefficient (sig. 0.000). This finding confirms that the stronger students' belief in the values ​​of Pancasila, the higher their assertiveness in rejecting various forms of radicalism that have the potential to threaten national unity.